The Leading Eikonal of the Scattering Amplitude of Particles in Gravitational Field at High Energy Using the Partial Wave Method - Han, Nguyen Suan; Xuan, Nguyen Nhu (VNU Journal of Science: Mathematics - Physics; Vol 33 No 1, 2017)
Abstract : The scattering amplitudes for two spineless particles colliding at Planckian center-of-mass energies are considered by the partial wave method in quantum gravity. In the framework of the partial method, a scheme for finding the leading eikonal scattering amplitudes is developed and constructed. The connection between the solutions obtained by partial wave method, quasi-potential and functional approaches is also discussed.